THE INTERRELATIONSHIP BETWEEN THE STATE OF HEALTH AND PSYCHOPHYSIOLOGICAL CHARACTERISTICS OF SERVICEMEN - Kalnysh, V.V.; Pashkovsky, S.M.; Maltsev, O.V.; Печиборщ, В.П.; Yeshchenko, O.I.; Shepitko, K.V. (World of Medicine and Biology, 2019)
The paper is devoted to revealing the psychophysiological prerequisites of transforming the state of professional health of servicemen, as well as to developing the algorithm of assessing this state on its basis. By means of the software and hardware complex the psychophysiological research has been conducted in 96 pilots and flight navigators who participated in combat actions. The following factors have been registered: the critical frequency of light flashes, the time of simple and complex visual and motor reflex, the functional motility of neuronal processes, the time of simple and complex auditory and motor response, the response to the movable object and other psychophysiological indices. By using the factor analysis the three insidious factors which account for the 35.1% of dispersion of the analyzed characteristics have been revealed. The following factors which describe the fundamental states of human body are revealed: the level of tiredness, alertness and persistency. The revealing and qualitative assessment of these characteristics make it possible to account for the body psychological qualities whose aggravation serves as the prerequisite for developing the negative abnormalities in the state of health of servicemen, as well as to use these values for the prognostication and timely prevention of the potential possibility of eventual negative changes in their health. The authors specify the psychophysiological factors which describe the functional state of servicemen who participated in combat actions. They also show that the factor value of such factors as’ vigor - fatigue’, ‘ activation’, and ‘ endurance – weakness’ significantly differ in servicemen with satisfactory state of health, as compared to to those having negative disturbances of this parameter. They have also developed the rules which make it possible to assess the state of health of servicemen according to the complex of psychophysiological indices with up to 70% accuracy.
Keywords: health; psychophysiological state; psychophysiological qualities; pilots; participants of combat actions